Preventive Criminal Policy Approaches to Reducing Juvenile Delinquency in Iraqi Legislation - Hadi Khudair, Researcher. Ghufran; Hammad Hamid, Prof.Dr. Hassan (Basra studies journal, 2025)
It is well established among criminal law scholars that punitive legislation typically intervenes only after a violation of the law has occurred. However, preventive criminal policy in juvenile legislation has marked a significant shift toward protecting minors from delinquency before it arises. This is evident in the effective Iraqi Juvenile Welfare Law No. 76 of 1983, which explicitly addresses such cases. Modern criminal policy can expand its scope to confront juvenile delinquency at earlier stages through preventive measures adopted by the legislator. These measures aim to provide more effective protection against emerging deviant behaviors and to safeguard minors from drifting into delinquency.